PENGARUH METODE PENGERINGAN TERHADAP KANDUNGAN GIZI IKAN LAYANG (Decapterus sp) - Marianus Ada Lein; Maria Magdalena Nona Motu Tukan; Fitriah Khairul (Universitas Teuku Umar, 2026)
Scad fish (Decapterus sp) is a high-value pelagic fishery commodity in Indonesia, widely known for its abundance and high nutritional content. However, different drying methods can significantly affect its nutritional quality. This study aims to determine the effect of drying methods on the nutritional composition of Scad fish. The research employed a comparative study with two treatments: traditional sun-drying and oven-drying. The study was conducted in October 2024, with sample preparation carried out at the Larantuka Institute of Teacher Training and Technology, and nutritional analyses performed at the Feed Chemistry Laboratory of Nusa Cendana University, Kupang. The analyses were conducted using standard methods: gravimetric for moisture content, dry combustion for ash content, Soxhlet for fat content, Kjeldahl for protein content, and by-difference calculation for carbohydrate content. The results demonstrated that drying methods significantly affected moisture, ash, fat, protein, and carbohydrate content of the Scad fish. The oven-drying method yielded the best nutritional profile, with moisture content of 14.337%, ash content of 36.00%, fat content of 9.187%, protein content of 53.262%, and carbohydrate content of 1.551%.Keywords: Decapterus sp; gravimetri; kjeldahl; Oven; Soxhlet: Solar Thermal